(untitled) (Annals of Bangladesh Agriculture, 2025)
A comprehensive review study has been conducted to address malnutrition problems prevailing over two billion global populations due to poor intake of daily diet especially vegetables. As a rich and easy source of essential nutrients like vitamins, minerals and other necessary phytochemicals, vegetables are considered as a sustainable dietary solution to this global problem, particularly for the vulnerable populations of developing countries. This study focuses on the deferent aspects of vegetables nutri-fortification conventional to molecular breeding, agronomic intervention to modern biotechnology and genetic engineering as well. The results of the research of different scientists revealed the efficacy of different conventional and molecular breeding to enrich concentration of iron, zinc, vitamin A etc., in different vegetable species and cultivar. Conventional agronomic practices like foliar application or inoculation of micronutrients have been found to be effective for improving nutrient content in leafy vegetables. Modern biotechnological interventions, including genetic engineering and genome editing, enable targeted manipulation of nutrient pathways, although they face challenges in regulatory and public acceptance. Application of plant growth promoting rhizobacteria, mycorrhizal fungi or other beneficial microorganisms have also shown promising results to enhance nutrient uptake in vegetables as well as improving soil-plant interactions. Beyond the successes, several limitations also found such as limited bioavailability, complex nature of genetic-environmental interactions, socio-economic obstacles as well as technological scalabilities are pronounced to speed up these programs. The study revealed the necessities of integrated, interdisciplinary approaches that combine crop science, soil health management as well as policy framework to promote speedy adoption of biofortified vegetables addressing this malnutrition. Ann. Bangladesh Agric. 28(2): 155-171